Musicogenic Epilepsy and Treatment of Affective Disorders: Case Report and Review of Pathogenesis. Issue 4 (December 2016) - Cheng, Jocelyn Y.
Abstract : Musicogenic epilepsy is a rare syndrome in which music triggers seizures. Affective network processing appears to play a key role in epileptogenesis. Many people with epilepsy suffer from comorbid affective disorders, the shared basis of which involves similar pathophysiologies, including deficiencies of serotonergic and noradrenergic function. Seizures and mood disorders may thus have reciprocal effects on one another, particularly in emotionally precipitated syndromes such as musicogenic epilepsy. I report a man with long-standing depression and anxiety who developed focal epilepsy that evolved into musicogenic seizures. His case suggests a pathophysiologic basis for this shared phenomenon.